2022
DOI: 10.3389/fcvm.2022.794445
|View full text |Cite
|
Sign up to set email alerts
|

An Updated Meta-Analysis of the Relationship Between Helicobacter pylori Infection and the Risk of Coronary Heart Disease

Abstract: BackgroundCoronary heart disease (CHD) is one of the leading causes of mortality in the world. Although the traditional risk factors for CHD have been identified, it seems that there are still many CHD cases without these factors. Previous studies have hypothesized that Helicobacter pylori (H. pylori) infection was associated with the risk of CHD.ObjectiveThe association between H. pylori infection and the risk of CHD was studied using a systematic evaluation and meta-analysis method.MethodsIn order to find re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 78 publications
2
14
0
2
Order By: Relevance
“…Fang et al included 48 studies, involving 7522 cases and 8311 controls for analysis, and reported that H. pylori infection was associated with an increased risk of ACS (OR = 2.03, 95% CI 1.66–2.47) 83 . Similarly, Tong et al included cross‐sectional and cohort studies for analysis, and showed that patients with positive anti‐ H. pylori IgG were significantly associated with an increased risk of CHD (OR, 1.58; 95% CI: 1.34–1.87) 84 . These meta‐analyses were limited by their inclusion of cross‐sectional studies, as well as studies without adjustment of other potential cardiovascular risk factors, therefore, the magnitude of the association between H. pylori infection and risk of CVD may be overestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Fang et al included 48 studies, involving 7522 cases and 8311 controls for analysis, and reported that H. pylori infection was associated with an increased risk of ACS (OR = 2.03, 95% CI 1.66–2.47) 83 . Similarly, Tong et al included cross‐sectional and cohort studies for analysis, and showed that patients with positive anti‐ H. pylori IgG were significantly associated with an increased risk of CHD (OR, 1.58; 95% CI: 1.34–1.87) 84 . These meta‐analyses were limited by their inclusion of cross‐sectional studies, as well as studies without adjustment of other potential cardiovascular risk factors, therefore, the magnitude of the association between H. pylori infection and risk of CVD may be overestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with angina pectoris have higher titers of anti-CagA antibodies compared to healthy controls [ 21 ]. Meta-analyses show an increased risk of atherosclerosis [ 26 ] as well as cardiovascular diseases, e.g., ischemic stroke and myocardial infarction, among H. pylori -positive subjects [ 20 , 27 ]. H. pylori -specific DNA has been detected in coronary atherosclerotic plaques [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tali e colaboradores comprovaram mediante a angiografia de cateterismo cardíaco que de 62 pacientes avaliados com DCC grave (portadores de estenose coronária ≥ 75%), 30 apresentaram anticorpos anti -H.Pyori Igg positivo, demonstrando assim uma franca relação entre as DCV´s e os processos infecciosos (Tali, et al, 2022). Do mesmo modo que (Matusiak, et al, 2016), (Sun, et al, 2016) e (Tong, et al, 2022), esse estudo também corrobora que a presença do DNA de HP em placas ateroscleróticas representa um achado patognomônico e possivelmente preditor de risco cardiovascular.…”
Section: Associação Entre a Infecção Pelo Hp E A Doença Coronariana I...unclassified
“…Da mesma forma que hipertensão arterial sistêmica (HAS), a obesidade, as dislipidemias e o tabagismo representam fatores de risco (FR's) tradicionais que aumentam a susceptibilidade para a DAC, os estudos também apontam o papel que as infecções crônicas exercem para o surgimento de eventos cardiovasculares (Tong, et al, 2022). Ainda assim, a literatura científica estabelece a necessidade de maiores investigações acerca da relação entre as coronariopatias e a existência de infecção prévia por HP, sendo imprescindível a busca por mais esclarecimentos no que concerne a esse tema.…”
Section: Introductionunclassified